Effects of blockage ratio and pitch ratio on thermal performance in a square channel with 30° double V-baffles - Jedsadaratanachai, Withada; Boonloi, Amnart (My University, 2014)
This article presents flow configurations and heat transfer characteristics in an isothermal square channel with 301 double V-baffles. The influences of blockage ratios (b/H, BR=0.05-0.25) and pitch ratios (L/H, PR=1-2) for Reynold numbers, Re=100-1200 are investigated numerically. The 30° double V-baffles are placed on both two opposite walls of the square channel with in-line arrangement and each V-tip pointing downstream. The numerical results are presented in four parts; accuracy validations, flow structures, heat transfer behaviors and performance evaluations. It is found that the use of the double V-baffles performs higher heat transfer rate and pressure loss than the smooth channel with no baffle. The rise of the blockage ratio and reducing the pitch ratio lead to the increase in heat transfer rate and pressure loss. The optimum thermal enhancement factor is found to be about 3.2 at PR=1, BR=0.10 and Re=1200.
Keywords: Double v-baffles; Heat transfer; Periodic flow; Thermal enhancement factor; V-downstream